Strategic Drivers of Academic Career Success in Private Higher Education - Wayan Arya Paramarta; Ida Bagus Udayana Putra; Ida Bagus Gede Udiyana (Jurnal Ekonomi dan Bisnis Jagaditha, 2026)
This study explores the strategic drivers of academic career success among lecturers in private higher education institutions (HEIs) in Bali, Indonesia. Drawing upon Human Capital Theory and the Policy Implementation Process Theory, the research examines how academic leadership influences career success both directly and indirectly through two key mediating variables: teamwork quality and learning agility. Using a quantitative approach, data were collected from 265 lecturers using proportionate stratified random sampling across various private HEIs in Bali. Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS 4 was employed to test the hypothesized relationships. The results reveal that academic leadership has a significant and positive effect on career success. Moreover, teamwork quality and learning agility serve as complementary mediators that strengthen the impact of leadership on lecturer career advancement. The findings underscore the importance of empowering academic leaders at the program level, fostering collaborative team environments, and developing lecturers’ learning agility through reflective and adaptive practices. Practically, the model suggests that institutional investment in team-based research environments is as critical as formal leadership development programs in accelerating academic career progression. This study contributes to the literature by integrating two theoretical perspectives into a single structural model and applying it in the under-researched context of private higher education in Indonesia. The novelty of this research lies in its holistic approach to lecturer career advancement, particularly in addressing challenges specific to private HEIs in developing regions.